Pengendalian Kualitas Menggunakan Metode Six Sigma (Studi Kasus pada PT Diras Concept Sukoharjo) - Hani Sirine; Elisabeth Penti Kurniawati (UII, 2017)
Quality control is important thing to be done by a company to minimize the defective product. Companies can analyze product defects by using six sigma method, by formulating Define, Measure, Analyze, Improve, Control (DMAIC) that occurred. The purpose of this study was to determine how the quality control using six sigma method is applied in a manufacturing company. The results showed that company which became the research object has an average of 0.34% product defects, it means that its cost of poor quality is less than 1% of sales. This shows that the company has reached six sigma, which means that the company actually has done a very good quality control. Based on this research, recommendation that can be given are the company needs to put quality control at every stage of the production process, train the workforce, conduct the quality contracts with suppliers so that supplied materials have excellent quality and provide an adequate storage (warehouse) to maintain the material quality.Â